2023
DOI: 10.1021/acsapm.2c02225
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Cured Norbornylized Seed Oil Epoxides for Sustainable, Recyclable, and Reprocessable Thermosets and Composite Application

Abstract: Reprocessable and recyclable thermosets were produced from the epoxidized norbornene seed oils (soybean oil and linseed oil). The epoxides were copolymerized using disulfidebased aromatic carboxylic acid to mold thermosets and composites. Both the neat and reprocessed thermosets were characterized for cross-linking efficiency by dynamic mechanical analysis (DMA), Soxhlet extraction, and swelling tests; for thermal stability by thermogravimetric analysis (TGA); and for T g by differential scanning calorimetry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…The use of biomass filler increases a system's biobased content, reduces costs and reduces weight, one of these organic nanofillers being cellulose. 64 The demand for fiber-reinforced composite materials is increasing because of their exceptional low weight, high weight-to-strength ratio and long-term durability properties. As a result, the next generation of biobased polyurethanes must be economical and based on nondepletable biobased resources.…”
Section: Biodegradable Polyurethane Synthesis With Epoxidation Techni...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of biomass filler increases a system's biobased content, reduces costs and reduces weight, one of these organic nanofillers being cellulose. 64 The demand for fiber-reinforced composite materials is increasing because of their exceptional low weight, high weight-to-strength ratio and long-term durability properties. As a result, the next generation of biobased polyurethanes must be economical and based on nondepletable biobased resources.…”
Section: Biodegradable Polyurethane Synthesis With Epoxidation Techni...mentioning
confidence: 99%
“…These unsaturated bonds are highly desirable for this type of application as they can be chemically modified through epoxidation to increase reactivity toward further polymerization. The use of biomass filler increases a system's biobased content, reduces costs and reduces weight, one of these organic nanofillers being cellulose 64 . The demand for fiber‐reinforced composite materials is increasing because of their exceptional low weight, high weight‐to‐strength ratio and long‐term durability properties.…”
Section: Biobased Polyurethanes: a Better Alternative To Conventional...mentioning
confidence: 99%
“…In addition, Alice Mija, [28][29][30] Jomin Thomas 31,32 et al reported the application of bio-based or vegetable oil epoxide, which could potentially compete with waterborne systems.…”
Section: Introductionmentioning
confidence: 99%
“…It restricts the sustainable development and application of thermoset polymers 7,8 . In 2011, Leibler and colleagues introduced dynamic covalent bonds (ester bonds) into the cross‐linked network of fatty acid or anhydride cured epoxy resins by accelerating the exchange of esters using catalysts, so that the network can be reprocessed with constant cross‐link density, and named this material “vitrimer.” 9 Epoxy vitrimers have the potential to become a more sustainable polymer material option by demonstrating reprocessability and environmental friendliness during processing 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…9 Epoxy vitrimers have the potential to become a more sustainable polymer material option by demonstrating reprocessability and environmental friendliness during processing. 10,11 The curing kinetics and investigation of epoxy resins are an important issue of composite technology research, providing guidance and theoretical basis for the manufacturing forming and processing process of composites. There are various methods to study curing kinetics, such as differential scanning calorimetry (DSC), Fourier transform infrared (FTIR), and rheological analysis.…”
Section: Introductionmentioning
confidence: 99%